Wrestling soul - "Chandavarkar, Ganesh L." (Bombay, 1955)
Six years ago, I was asked by one for whom and whose word I have the highest reverence to write in English a short biography of Sir Narayan Chandavarkar. I was, at that time, reading for my own benefit Narayanrao's diaries and his note books, and had made use of a portion of what I had read and meditated on for the discourses which I had to prepare for the Prayer Services held in the family in connection with Narayanrao's death anniversaries. Much as I wished to take up the task which was suggested to me, I had considerable misgivings about my own limited capacity. I hesitated a good deal. I feared that what was lofty and grand might seem to lose some of its loftiness and grandeur because of its contact with the feebleness of my attempt. During the last six years, however, I gathered confidence from the thought that the contact with the lofty and grand character itself would trans form the feebleness of my attempt into strength. In Decem ber of last year, I was once again asked to take up the task and, this time, I felt bold enough to do so.
Keywords: "Chandavarkar , Narayan biography"